Physics II for dummies - Holzner, Steven (Hoboken, NJ : Wiley, 2010)
You don't have to be Einstein to understand physics. This plain-English guide walks you through the essentials and gives you easy-to-understand information on this often-intimidating course.
Understanding physics fundamentals. Understanding your world : Physics II, the sequel ; Gearing up for Physics II -- Doing some field work : electricity and magnetism. Getting all charged up with electricity ; The attraction of magnetism ; Alternating current and voltage -- Catching on to waves : the sound and light kinds. Exploring waves ; Now hear this : the word on sound ; Seeing the light : when electricity and magnetism combine ; Bending and focusing light : refraction and lenses ; Bouncing light waves : reflection and mirrors ; Shedding light on light wave interference and diffraction -- Modern physics. Heeding what Einstein said : special relativity ; Understanding energy and matter as both particles and waves ; Getting the little picture : the structure of atoms ; Nuclear physics and radioactivity -- The part of tens. Ten physics experiments that changed the world ; Ten online problem-solving tools.
Includes index.
Keywords: Physics